Redesain UI/UX Fitur Privasi Mute, Restrict, dan Unfollow pada Instagram Berbasis Model Mental Pengguna - MUHAMAD RIFKI ALFADHRY; Gugun Gunadi; Susi Maulidiah (Fakultas Teknik Universitas Persada Indonesia YAI, 2026)
Instagram reaches approximately 108 million users in Indonesia (DataReportal, 2025), making the Mute, Restrict, and Unfollow features important tools for managing social interaction and protecting user privacy. Previous usability studies (Sidik, 2025; Huda et al., 2023; Nyoman et al., 2025) have confirmed usability problems on Instagram, yet none has produced an interface redesign grounded in a mapping of users' mental models toward these three specific features. This study aims to redesign the UI/UX of the Mute, Restrict, and Unfollow features using a Design Thinking approach grounded in user mental model analysis, and to evaluate its effectiveness using the System Usability Scale (SUS). The research began with a preliminary study involving 15 active Instagram users, followed by semi-structured interviews and Think-Aloud Protocol sessions with 13 participants during the Empathize and Define stages, and a SUS-based evaluation of a high-fidelity prototype during the Prototype stage. The preliminary study found that 80% of respondents could not correctly understand the functions of the Mute and Restrict features. The interviews further revealed a mismatch between users' mental models and the system's actual mechanisms, causing confusion when managing interactions. Based on these findings, an interface redesign was developed, resulting in a SUS score of 88.65 (Excellent category), surpassing the contextual benchmark of 66.57 established by a prior study (Sidik, 2025). These findings indicate that a Design Thinking approach grounded in user mental model mapping can produce a UI/UX design that is easier to understand, reduces cognitive load, and strengthens users' privacy control on Instagram.